The Influence of Income Shifting Incentives towards The Tax Haven Country Utilization: Case Study on the Companies listed in Indonesian Stock Exchange - Nurhidayati Nurhidayati; Hendyga Fuadillah (Institute of Research and Community Outreach - Petra Christian University, 2018)
This study aims to determine the association between a series of income shifting incentives, including multinationality, transfer pricing aggressiveness, thin capitalization, intangible assets, and tax haven country utilization. This study is based on a sample of 78 multinational companies listed on the Indonesia Stock Exchange over 2012–2016 period (390 firm-year). The results prove that, multinationality, thin capitalization, intangible asset are positively associated with tax haven utilization, while transfer pricing aggressiveness is not positively associated with tax haven utilization. Based on the additional analysis, basic and chemicals sectors have the highest association between a series of income shifting incentives and tax haven utilization among other industrial sectors and each industry sector has different ways of utilizing tax haven country. The findings of this study are expected to provide input to the Directorate General of Taxes the importance of reviewing debt to equity ratio rule which turned out to be one gap for the taxpayer and in making the proposed inspection plan and the potential thematic exploration related to profit shifting incentives more focused on basic industry and chemicals sector. The Directorate General of Taxes also needs to raise awareness of the taxpayers of agriculture, mining, basic and chemicals, and trade, service and investment, which has a growing number of subsidiaries in tax haven country. Increased supervision of intangible assets transfers in the agriculture and infrastructure, utilities & transportation sectors also needs to be done.